Sistem Kontrol Keseimbangan Robot Beroda Dua Pada Kondisi Bergerak Maju - Silfani L. Tobing; Sujono Sujono (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2019)
In this research designed a two-wheeled robot's balance using the Arduino Pro Mini 328P as controllers, sensors, ultrasonic distance sensor is used as well as ultrasonic sensor is used as slope detection robots, the driver of the motor and the dc motor L298 as mover of the robot. The robot system is designed to be able to avoid the existing wall before him who is regarded as a deterrent, and is able to detect the tilt which occurs on the robot. This testing is done in 4 different positions, as the robot moves forward from the start, the robot will detect the existing wall before him, and then the robot will turn to the right and back to move forward, and if the robot again to detect the robot's wall will move backwards and turn to the left. Of the system that has been created and fully tested, the robot would avoid the walls and not hit the wall.